Reliable and Faster Data Communication in MANET and VANET Based on Localization and Clustering Techniques - Pattnaik, Omkar; Kumar Pattanayak, Binod; ., . (International Journal of Engineering and Technology, 2018)
The concept of VANET (Vehicular Ad hoc Network) is derived from the idea of MANET (Mobile Ad hoc Network), where each vehicle is considered as a mobile node. Localization technique based on the clustering methods is an important issue for both MANET and VANET. To find out the position of a node and also provide the link stability in the ad hoc network is a present research area from the researcher view. Now-a-days a large spectrum of work has already been done in clustering techniques in ad hoc network, especially in VANET. The clustering technique is very much useful for reliable and faster data communication in both the forms of networks. The objective of this paper is to provide an idea about the localization concept related to clustering method based on both GPS and GPS free situations in real world scenario.Â